Stabilised decellularised vascular grafts in an ovine carotid model - Mentor, Keno (Department of Surgery, 2019)
Background: There is an urgent clinical need for an alternative vascular graft, especially for smaller artery applications such as in below-knee and coronary artery bypass. Currently available synthetic grafts have unacceptably low patency rates, while autologous saphenous vein grafts are not feasible in one third of patients. Decellularised vascular grafts have been investigated as alternative conduits, but this chemical treatment results in degradation of the extracellular matrix. Chemical stabilization of elastin with penta-galloyl glucose (PGG) combined with collagen stabilisation during covalent heparinisation was previously investigated by our group in a small animal model and shown to be effective and safe. The current study describes their evaluation in a large animal (ovine) model. Methods: Porcine mammary arteries were harvested, decellularised according to an established protocol involving rinsing with sodium hydroxide, alcohol (ETOH), treatment with DNAse/RNAse enzymes, immersion in PGG and subsequently surface modified with covalently bound heparin. Samples of the grafts were also tested for radial and suture retention strength. The prepared grafts were implanted as interposition grafts into the carotid arteries of 6 sheep, using industry standard 6mm expanded polytetrafluoroethylene (ePTFE) on the contralateral side of each animal as control. In-situ patency was determined by ultrasound and angiography at two months, following which the grafts were explanted for macro- and microscopic analysis. Results: In-vitro evaluation: Grafts showed significant levels of bound heparin (14.56 mg/g vs 0.69mg/g in untreated tissue) and demonstrated similar mechanical properties to those of human carotid arteries. Survival: Five out of six sheep survived the full 2-month implant period, while the remaining animal developed sepsis shortly after implantation and was euthanized on day 4. Patency: None of the decellularised grafts were patent at explant, as assessed by ultrasound, angiography and macroscopic examination. Two of the five control (ePTFE) grafts were patent. Microscopic analysis: An inflammatory cell infiltrate with vascularised granulation tissue was found encasing the decellularised xenografts with little or no sign of endothelial cell infiltration. Signs of early occlusion, likely due to technical factors, was noted at the sites of anastomosis. Conclusion: Although demonstrating similar mechanical properties to human carotid arteries, and promising results in the small animal model, the stabilised decellularised vascular grafts failed to achieve endothelialisation or patency in this sheep carotid model. Significant calibre mismatch between the test graft and the native artery is thought to be the primary factor in the failure of these grafts, highlighting the potential difficulty in acquiring grafts of an appropriate size from animal sources.